STUDY OF FEATURES OF MICROFLORA OF PATIENTS WITH DISEASES OF THE ORAL MUCOSA. EVALUATION OF THE EFFICACY OF PRODUCTS BASED ON BACTERIOPHAGES "FAGODENT" IN THE TREATMENT OF CHRONIC APHTHOUS STOMA TITIS AND LICHEN PLANUS - E. A. Volkov; M. L. Polovets; K. E. Isadzhanyan; G. S. Pashkova; V. V. Nikitin; V. M. Popova; E. L. Zhilenkov (Исследования и практика в медицине, 2016)
Effective complex treatment of patients with pathology of the oral mucosa (OM) includes drug effects on pathogenic bacteria as a possible etiological factor in the development of these diseases.Purpose. Study of characteristics of oral microflora of patients with diseases of the OM, the efficiency of the national preventive agent for topical application "Fagodent" in the form of a gel based on bacteriophages in the treatment of chronic recurrent aphthous stomatitis and lichen planus.Materials and methods. In a pilot study (up to 3 months follow-up) they included 27 patients aged 19 to 80 years old with chronic recurrent aphthous stomatitis (CRAS) and lichen planus (LP). To monitor the efficiency of in vitro we carried out spot-testing for bacterial lawn.Results. Results showed the frequent detection of bacteria of the staphylococci and streptococci in smears obtained from the elements of defeat in the CRAS and LP, while the PCRdiagnostics detect the presence of rare parodontopatogenov on aftah and papules. The study of the effectiveness of products based on bacteriophages "Fagodent» in vitro showed a high sensitivity of the pathogens to bacteriophages gel "Fagodent" when exposed to cultures derived from patients with CRAS. The use of prophylactic agents based on bacteriophages in the treatment of chronic recurrent aphthous stomatitis significantly reduced pain, accelerated the relief of the inflammatory process to reduce the time of repair. Application means "Fagodent" in the complex treatment of lichen planus is not significantly affected the course of the disease.Conclusion. The laboratory research and clinical observations confirm the effectiveness and appropriateness of products based on bacteriophages "Fagodent" in the treatment of chronic aphthosous stomatitis.